2007
DOI: 10.1093/hmg/ddm070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and investigation of single nucleotide polymorphisms and a novel TLR2 mutation in the human TLR2 gene

Abstract: In the innate immune system, TLR2 plays a central role for the response to a wide variety of microbial and endogenous danger signals. A considerable number of genetic polymorphisms within the human TLR2 gene have been reported in non-coding and coding sequences. Except for the Arg753Gln variant, however, their clinical relevance is unclear and the assessment of the effects of amino acid substitutions on receptor function is lacking. In the present study, we have characterized all known single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 28 publications
5
29
2
1
Order By: Relevance
“…Stable transfectants were selected with 1 g/ml blasticidin and maintained on poly-D-lysine-coated tissue culture plates (BD Biosciences). Transfection efficiency of the different clones was comparable with previous findings from other cell types (31), as tested by Western blotting and immunohistochemistry with anti-HA (InvivoGen; Cell Signaling). Caco-2 controls (mock) were untransfected cells without any exogenous DNA.…”
Section: Animals-mdr1␣supporting
confidence: 82%
“…Stable transfectants were selected with 1 g/ml blasticidin and maintained on poly-D-lysine-coated tissue culture plates (BD Biosciences). Transfection efficiency of the different clones was comparable with previous findings from other cell types (31), as tested by Western blotting and immunohistochemistry with anti-HA (InvivoGen; Cell Signaling). Caco-2 controls (mock) were untransfected cells without any exogenous DNA.…”
Section: Animals-mdr1␣supporting
confidence: 82%
“…The TLR2 gene, mapped to chromosome 4q32, consists of 3 exons. Three major functional polymorphisms Pro631His, Arg677Trp, and Arg753Gln have been described in the Caucasian population (25,38,39). However, these SNPs are absent in our screening population, consistent with the HapMap database and another report (28).…”
Section: Discussionsupporting
confidence: 91%
“…Mice without TLR2 are hyporesponsive to Gram-positive bacterial cell wall components . A number of SNPs in TLR2 have been reported in the extracellular domain [R753Q , Y715K, and Y715stop (Merx et al, 2007)] and the cytoplasmic domain [P631H (Smirnova et al, 2003)]; although the extracellular domain mutations result in decreased activity of TLR2 to Gram-positive bacterial ligands Schröder et al, 2003), the genetic evidence linking these SNPs with a susceptibility to Gram-positive infections is unclear (Schröder and Schumann, 2005). Twelve SNPs in TLR1 [of these, S248N, H305L, P315L (Johnson et al, 2007), and I602S (Johnson et al, 2007) have defective signaling] and 14 SNPs in TLR6 (Johnson et al, 2007) have also been identified.…”
Section: Toll-like Receptor 2: Agonism and Antagonismmentioning
confidence: 99%